2017
DOI: 10.7897/2230-8407.080444
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Development and Evaluation of Bio-Adhesive Carbopol 974p Nf Polymer Matrix Based Sustained Release Gliclazide Tablet

Abstract: The aim of the present study was to develop a sustained release bio-adhesive matrix based Gliclazide tablet to match the in-vitro and ex-vivo experimental profile, and can be used to the treatment of Type II Diabetes Mellitus. It will be expected that single Gliclazide tablet reduce glycosylated hemoglobin and overcoming individual large fluctuation of oral bioavailability. Eleven types of tablets were formulated by wet granulation technique which contains 30 mg of Gliclazide and different concentrations of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similar to our results, Anisuzzman et al reported that the flow and compressibility values of the powders improved by increasing the amount of HPMC and Carbopol in the formulations. In addition, when the formulations containing the same amount of HPMC and Carbopol are compared, it was seen that the formulations containing Carbopol have better flow and compressibility compared to HPMC (28). The angle of repose values of the formulations (F1 and F2) prepared with HPMC/Carbopol and PEO were found to be similar and less than the other polymers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to our results, Anisuzzman et al reported that the flow and compressibility values of the powders improved by increasing the amount of HPMC and Carbopol in the formulations. In addition, when the formulations containing the same amount of HPMC and Carbopol are compared, it was seen that the formulations containing Carbopol have better flow and compressibility compared to HPMC (28). The angle of repose values of the formulations (F1 and F2) prepared with HPMC/Carbopol and PEO were found to be similar and less than the other polymers.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies showed the effectiveness of HPMC and Carbopol for providing controlled drug release profile (34). When the drug release amount of two different formulations containing HPMC and Carbopol in the same amount was compared, it was observed that Carbopol decreased drug release compared to HPMC (28). In addition, it has been proven by the use of Carbopol and HPMC in formulations that it reduces the dose dumping effect and is suitable for ER formulations (35).…”
Section: Discussionmentioning
confidence: 99%